1983
DOI: 10.1042/cs0650149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of ZK 36374, a Stable Prostacyclin Analogue, on Adhesion of Rabbit Platelets to Damaged Aorta and Serotonin Release by Adherent Platelets

Abstract: The effects of ZK 36374, a prostacyclin analogue, were studied on adhesion of rabbit platelets to damaged rabbit aorta and on activation of platelets (judged by release of serotonin and formation of thromboxane-B2) in response to the processes of adhesion to the vessel surface and aggregation in response to microfibrillar collagen in suspension. In the presence of ZK 36374 (10-100 nmol/l), platelet adhesion and thromboxane-B2 formation were progressively reduced. The extent of serotonin release from adherent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1984
1984
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…19 Platelet-rich plasma was separated by centrifugation at 200 g for 9 min. The platelet-containing supernatant was removed and centrifuged at 1500g for 20 min to obtain a platelet pellet.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…19 Platelet-rich plasma was separated by centrifugation at 200 g for 9 min. The platelet-containing supernatant was removed and centrifuged at 1500g for 20 min to obtain a platelet pellet.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Außerdem erfolgt die hypotherme Perfusion der Niere gleichmäßiger und sorgt für einen guten Wärmeaustausch, der für die nachfolgende Lagerungskonservierung bei 4 °C notwendig ist. 17,18,20,24,25,26). Die Bildung von Thrombozytenaggregaten, vor allem im Bereich der Aa.…”
Section: Diskussionunclassified
“…ZK 36374 (Iloprost) is a chemically stable analogue of PGI2 that also inhibits platelet aggregation. Studies of its effects on blood platelets in vitro have shown that it is at least as potent as PGI2 (5)(6)(7). However, studies in animals (8) and in man (9) have indicated that its effects on the circulation may be less profound than those of PGI2.…”
Section: Introductionmentioning
confidence: 99%